(3GdQhV GdGfa aj TQM ZQjH GdSjQs - (3GdSgjdj , YHO GdQMef Hf YHO Gddg Hf CMeO Hf GUHZ GdNKYej CHh GdbGSe, CHh GdbGSe,J (B581 (3g` s ((3YeQ Hf GHQGgje Hf ehSi s)
(3ChdgG (B:s
(3aUd hPcQ GHf GSMGb ajef GSJgTO jhe CMO YHjO GHf GdJjgGf hGSe GdJjgGf eGdc hde jQaY fSHg s
(3BNQgG (B:s
(3hdf jHdZ HGdEWfGH ai eOM hdG QKGA cfg eMGSfg Ydjg GdSdGe ced GdSaQ GdKGdK ef QhV GdCfa hGdMeO ddg QH GdYGdejf s
(3GdLRA GdKGdK gh GdCNjQs
(3Ydjg Jedcs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJGQjNs